Transverse versus longitudinal incision for minimally invasive Achilles tendon repair. Issue 3 (14th September 2018) - Bohl, Daniel; Barnard, Eric; Movassaghi, Kamran; Hamid, Kamran; Schiff, Adam
Category: Sports Introduction/Purpose: The rate of wound complications following traditional open Achilles tendon repair is reported at 7-8%. In an effort to reduce the rate of wound complications, orthopaedic surgeons have adopted novel minimally invasive techniques. The purpose of this study is to characterize the rate of wound and other early complications following a minimally invasive Achilles tendon repair, to identify any factors associated with increased risk. Methods: The postoperative courses of 55 patients who underwent minimally invasive Achilles tendon repair by two surgeons at separate academic medical centers were retrospectively reviewed. Repair technique was similar in all cases, making use of the same commercially available suture-guidance jig, silicone-impregnated deep suture material, and locking stitch technique. However, 31 procedures used a longitudinal incision and a tourniquet (one surgeon's preference), while 24 procedures used a transverse incision and no tourniquet (the second surgeon's preference). Of the 24 procedures using transverse incisions, 2 had to be converted to L-shaped incisions to achieve better access to the tendon. The rates of early complications within 3 months after surgery were characterized and compared between patients with differing procedural characteristics. Results: Of the 55 patients included in the study, 2 (3.6%) developed wound complications. Both wound complications appeared to be reactions to the deep suture material (see Table 1 for details). There was no statistical difference in the rate of wound complications between patients in the longitudinal incision/tourniquet group and patients in the transverse incision/no tourniquet group (6.5% versus 0.0%; p=0.499). Three patients (5.5%) developed sural neuropraxia, which manifested as mild-to-moderate subjective numbness with sensation remaining intact to light touch. There were no cases of re-rupture. At 3-month follow-up, all 55 patients had intact Thompson tests and well-healed wounds. Conclusion: The rate of wound complications following minimally invasive Achilles repair is low at 3.6%. The present study could not demonstrate a difference in risk for wound complications between patients treated with a longitudinal incision and tourniquet and patients treated with a transverse incision and no tourniquet. The wound complications we observed were primarily attributable to inflammatory reactions to the silicone-impregnated deep suture material. Patients should be counseled that although risk for wound complications may be lower with minimally invasive techniques, such techniques do risk sural neuropraxia and deep suture reaction. Further prospective analysis is warranted.